Mortality in Three-Toed Box Turtles (Terrapene mexicana triunguis) at Two Sites in Missouri - Palmer, Jamie L.; Brenn-White, Maris; Blake, Stephen; Deem, Sharon L. (Frontiers in Veterinary Science, 2019)
Once ubiquitous, North American box turtles are experiencing reductions in abundance and range, but the magnitude of these losses is largely unknown. In Missouri, native box turtles (Terrapene mexicana triunguis and Terrapene ornata ornata) are declining across the state due to anthropogenic disturbances such as urbanization, habitat fragmentation, and vehicle collisions. Through radio-tracking over a period of seven years, we documented the survival of adult three-toed box turtles at two sites in Missouri: Forest Park (urban park) and Tyson Research Center (a protected rural forest). Estimated annual survival of adult turtles in Forest Park was 79% (95% CI: 0.68-0.87) while at Tyson Research Center annual survival was 93% (95% CI: 0.83-0.97). The odds of annual survival for a turtle at Tyson Research Center were 3.5 times that of a turtle living in Forest Park. “Winter kill”, which refers to box turtles found on the surface during brumation or within two weeks of emergence, was the most frequently documented category of mortality in Forest Park. At Tyson Research Center, winter kill was not documented; however, the reasons for most deaths were unknown. These data raise the question about the potential of large urban parks as refuges for box turtles, which we may answer by future studies that compare box turtles living in multiple urban and rural settings. Our preliminary data suggest that even the largest urban parks may not sustain populations of box turtles which has severe implications as urbanization continues to degrade and eliminate box turtle habitat throughout their range.